Polyester material composite microsphere, leather filler and preparation method
By controlling the molecular weight ratio of polyester materials and loading functional proteins, a stable three-dimensional network structure is formed, which solves the problems of microsphere aggregation and acidic substance accumulation of polyester material microsphere fillers, and achieves the synergistic effect of skin repair and collagen regeneration.
Patent Information
- Application Number
- CN202510810527.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-09-19
AI Technical Summary
Existing polyester microsphere fillers tend to aggregate during use, leading to nodular reactions, and degrade in the body to produce acidic substances that trigger inflammatory reactions.
By controlling the ratio of large and small molecular weight polyester materials and loading functional proteins, a stable three-dimensional network structure is formed. Cross-linking agents are used to form stable cross-links between the polyester material composite microspheres and sodium hyaluronate to resist pushing force and control the degradation rate.
It achieves controlled degradation of microspheres, avoids microsphere aggregation and acidic substance accumulation, provides synergistic effects of skin repair and collagen regeneration, and reduces inflammatory reactions and jamming during the pushing process.
Smart Images

Figure CN120661734A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a polyester material composite microsphere, a dermal filler and a preparation method thereof. Background Art
[0002] In recent years, the use of microsphere fillers to promote the body's regeneration of collagen and elastin has been rapidly developed, but most of these products are polyester microspheres suspended in carboxymethyl cellulose or sodium hyaluronate matrix materials. Microsphere aggregation is prone to occur during the push injection process, which leads to needle clogging and adverse reactions such as nodules after implantation. In response to the above problems, clinical practice often uses dilution and reduction of single-point injection volume to reduce the probability of adverse reactions, but it still cannot completely solve the above problems. Patent CN117838922A discloses an amino-modified left-handed polylactic acid drug-loaded microsphere and its preparation method and application. A layer of polylysine is uniformly coated on the surface of the left-handed polylactic acid microsphere to obtain amino-modified left-handed polylactic acid drug-loaded microspheres. The modified microspheres have the same charge, which can prevent the microspheres from approaching each other and play a certain role in preventing microsphere agglomeration. However, due to the limited charge force, the pushing force generated during the push injection and implantation process will destroy the charge force, and the phenomenon of microsphere aggregation will still occur.
[0003] Furthermore, polyester materials commonly used in the industry produce acidic substances during degradation in the body. Excessive accumulation of acidic substances in the body can cause tissue inflammation and cause pain to the user. Therefore, achieving a gradient degradation of polyester filler products and preventing excessive acidic accumulation is a pressing issue. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to address the deficiencies of the above-mentioned existing technologies and provide a polyester material composite microsphere, a dermal filler and a preparation method, so as to solve the problem that the microspheres of existing polyester material filler products are prone to aggregation and induce nodular reactions during use, while inhibiting the accumulation of acidic substances to avoid inflammatory reactions.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing polyester material composite microspheres, characterized in that it includes the following steps:
[0006] Step 101: dissolving a high molecular weight polyester material and a low molecular weight polyester material in an organic solvent to obtain a polyester material solution; adding the polyester material solution to an emulsifier solution, and homogenizing and emulsifying at 1000-3000 rpm to obtain polyester material microspheres; the mass ratio of the high molecular weight polyester material to the low molecular weight polyester material is 1:3-3:1;
[0007] Step 102: Add the polyester material microspheres described in step 101 to a mixed protein solution containing recombinant collagen and recombinant elastin, add crosslinker A, and stir the reaction system to obtain polyester material composite microspheres; the mass-to-volume ratio (W / V) of the polyester material microspheres and the mixed protein solution is 1:(2-5), where the unit of mass is g and the unit of volume is mL.
[0008] The above-mentioned method for preparing polyester composite microspheres is characterized in that the polyester material is one of polycaprolactone (PCL), poly L-lactic acid (PLLA), poly D-lactic acid (PDLA) or polylactic acid-glycolic acid copolymer (PLGA); the molecular weight of the high molecular weight polyester material is 1.8×10 4 ~3.0×10 4 Da, the molecular weight of the low molecular weight polyester material is 0.5×10 4 ~1.5×10 4 Da; the organic solvent is one of dichloromethane, ethyl acetate, acetone or chloroform; the mass fractions of the large and small molecular weight polyester materials in the polyester material solution are both 1% to 15%.
[0009] The above-mentioned method for preparing polyester material composite microspheres is characterized in that the emulsifier is polyvinyl alcohol (PVA), hydroxypropyl methylcellulose (HPMC), sodium lauryl sulfate (SDS) or Tween 80; the volume ratio of the polyester material solution to the emulsifier solution is 1:(2-25), and the mass fraction of the emulsifier is 0.01%-4%.
[0010] The above-mentioned method for preparing polyester composite microspheres is characterized in that the mass fraction of recombinant collagen in the mixed protein solution is 5% to 20%, and the mass fraction of recombinant elastin is 0.5% to 10%.
[0011] The above-mentioned method for preparing polyester material composite microspheres is characterized in that the crosslinking agent A is 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC), genipin or 3-mercaptopropane-N-hydroxysuccinimide ester (NHS ester); the mass fraction of the crosslinking agent A in the reaction system is 0.01% to 1%; the stirring speed is 50 rpm to 300 rpm, and the time is 0.5h to 2.5h.
[0012] Furthermore, the present invention provides a dermal filler, characterized in that the raw materials of the dermal filler include polyester material composite microspheres prepared by the above preparation method, and also include sodium hyaluronate solution and active ingredients.
[0013] The above-mentioned dermal filler is characterized in that the mass fraction of the sodium hyaluronate solution is 5% to 30%, and the mass-to-volume ratio (W / V) of the polyester composite microspheres to the sodium hyaluronate solution is 3:(2-27), where the unit of mass is g and the unit of volume is mL;
[0014] The above-mentioned dermal filler is characterized in that the active ingredients include one or more of the following ingredients: recombinant collagen, recombinant elastin, niacinamide, vitamin B1, vitamin B2, vitamin C, glycine, proline, lysine, tranexamic acid, polydeoxynucleotides and glutathione.
[0015] Furthermore, the present invention also provides a method for preparing the above-mentioned dermal filler, characterized by comprising:
[0016] Step 1: Add polyester composite microspheres to sodium hyaluronate solution and mix evenly, add crosslinking agent B, crosslink at 20-60° C. for 1-24 hours, and then wash to remove crosslinking agent residue to obtain a crosslinked gel;
[0017] Step 2: Add active ingredients to the cross-linked gel in step 1 to obtain a dermal filler.
[0018] The above method is characterized in that the crosslinking agent B in step 1 is divinyl sulfone, polyethylene glycol diglycidyl ether (PEGDE) or 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC), and the mass fraction of the crosslinking agent B in the reaction system is 0.5% to 5%.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. The polyester composite microspheres prepared by the present invention achieve controlled sequential degradation of the microspheres by precisely controlling the molecular weight and compounding ratio of the polyester material, thereby reducing the risk of tissue inflammation caused by the accumulation of acidic substances due to the concentrated degradation of the polyester material. In addition, the functional proteins loaded on the polyester composite microspheres constructed by the present invention contain active groups such as amino, carboxyl, and thiol groups, and the acetylamino, hydroxyl, and carboxyl groups in sodium hyaluronate form a stable three-dimensional network structure under the action of a cross-linking agent, fixing the microspheres inside the network structure. This can resist the pushing force during injection and the tissue pressure generated by injection into the body, avoiding the aggregation of microspheres during use, and the injection process is smooth and free of jamming.
[0021] 2. The dermal filler of this invention achieves precise, all-stage effects on the skin through the synergistic effects of polyester composite microspheres, sodium hyaluronate, and active ingredients. During the initial injection phase, the sodium hyaluronate and active ingredients in the product rapidly replenish lost matrix protein components, achieving excellent immediate results. As the filling process progresses, the functional proteins loaded into the microspheres and the sodium hyaluronate continue to work synergistically, enhancing skin repair capacity, reducing oxidative damage, and delaying skin aging. Furthermore, the polyester microspheres stimulate collagen regeneration in the skin while also promoting cellular metabolism, helping to maintain healthy skin.
[0022] The technical solution of the present invention is further described in detail below in conjunction with the embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Graph showing the in vitro degradation pH changes of the dermal fillers prepared in Examples 1-3 of the present invention and the fillers prepared in Comparative Examples 1-3;
[0024] Figure 2 Comparison of histological section results of dermal fillers prepared in Examples 1-3 of the present invention and fillers prepared in Comparative Examples 1-3 after subcutaneous implantation in New Zealand rabbits at 6M, 12M, 18M, and 24M depths;
[0025] Figure 3 Microscopic observation results (10X) of the squeezed samples of the dermal fillers prepared in Examples 1-3 of the present invention and the fillers prepared in Comparative Examples 4-7;
[0026] Figure 4 The pushing force test results of the dermal fillers prepared in Examples 1-3 of the present invention and the fillers prepared in Comparative Examples 4-7 are shown, where A: Example 1; B: Example 2; C: Example 3; D: Comparative Example 4; E: Comparative Example 5; F: Comparative Example 6; and G: Comparative Example 7. DETAILED DESCRIPTION
[0027] To further clarify the above-mentioned objectives, features, and advantages of the present invention, the following detailed description of specific embodiments of the present invention is provided with reference to the following examples. The recombinant elastin and recombinant collagen used in the present invention are commercially available products. Unless otherwise specified, the techniques used in the following examples are conventional methods well known to those skilled in the art. Materials and reagents used in the following examples are commercially available unless otherwise specified. The following examples further illustrate the present invention in detail, but the following description is not intended to limit the present invention.
[0028] Example 1:
[0029] Step 1: Preparation of polyester microspheres:
[0030] 1) Take the molecular weight (Mw) as 2.5×10 4 Da and molecular weight (Mw) are 1.0×10 4 Da PCL material was dissolved in dichloromethane solvent to form a polyester material solution, in which the mass fraction of PCL materials with different molecular weights was 10%; the mass ratio of high molecular weight PCL to low molecular weight PCL was 1:1;
[0031] 2) adding the polyester material solution to a 1% PVA aqueous solution and homogenizing twice at 1600 rpm to complete the preparation of polyester material microspheres, wherein the volume ratio of the polyester material solution to the PVA aqueous solution is 1:8;
[0032] Step 2: Add the polyester material microspheres to the mixed protein solution, then add EDC, and stir at 100 rpm for 1.5 hours to complete the preparation of composite microspheres, wherein the mass volume ratio (W / V) of the polyester material microspheres to the mixed protein solution is 1:3, the unit of mass is g, and the unit of volume is mL; the mass fraction of EDC in the reaction system is 0.5%; the mass fraction of recombinant collagen in the mixed protein solution is 10%, and the mass fraction of recombinant elastin in the mixed protein solution is 3%;
[0033] Step 3: Add the above composite microspheres to a 10% sodium hyaluronate solution and mix evenly. Add PEGDE, crosslink at 45°C for 4 hours, and then wash with ethanol to remove the crosslinker residue to obtain a crosslinked gel, wherein the mass-to-volume ratio (W / V) of the polyester composite microspheres to the sodium hyaluronate solution is 2:3, where the unit of mass is g and the unit of volume is mL; the mass fraction of PEGDE in the reaction system is 2.5%;
[0034] Step 4: Add the active ingredients recombinant elastin, recombinant collagen, glycine, proline, lysine, and polydeoxynucleotides to the cross-linked gel and mix thoroughly to obtain the final dermal filler. The active ingredients are recombinant elastin at a concentration of 2 mg / mL, recombinant collagen at a concentration of 10 mg / mL, and glycine, proline, lysine, and polydeoxynucleotides at a concentration of 3 mg / mL.
[0035] Example 2:
[0036] Step 1: Preparation of polyester microspheres:
[0037] 1) Take the molecular weight (Mw) as 1.8×10 4 Da of PLLA and molecular weight (Mw) is 0.5×10 4Da PCL was dissolved in ethyl acetate solvent to form a polyester material solution, in which the mass fraction of high molecular weight PLLA was 1% and the mass fraction of low molecular weight PCL was 3%; the mass ratio of high molecular weight PLLA to low molecular weight PCL was 1:3;
[0038] 2) adding the polyester material solution to a 0.01% HPMC aqueous solution and homogenizing at 1000 rpm for three times to prepare polyester material microspheres, wherein the volume ratio of the polyester material solution to the HPMC aqueous solution is 1:25;
[0039] Step 2: Add the polyester material microspheres to the mixed protein solution, then add genipin, and stir at 50 rpm for 0.5 h to complete the preparation of the polyester material composite microspheres, wherein the mass volume ratio (W / V) of the polyester material microspheres to the mixed protein solution is 1:5, where the unit of mass is g and the unit of volume is mL; the mass fraction of genipin in the reaction system is 0.01%; the mass fraction of recombinant collagen in the mixed protein solution is 5%, and the mass fraction of recombinant elastin in the mixed protein solution is 0.5%;
[0040] Step 3: Add the polyester composite microspheres to a 5% sodium hyaluronate solution and mix evenly. Then add EDC, crosslink at 20°C for 1 hour, and then dialyze and wash to remove the crosslinker residue to obtain a crosslinked gel, wherein the mass-to-volume ratio (W / V) of the polyester composite microspheres to the sodium hyaluronate solution is 1:9, where the unit of mass is g and the unit of volume is mL; the mass fraction of EDC in the reaction system is 0.5%;
[0041] Step 4: Add the active ingredients nicotinamide, vitamin B1, vitamin B2, vitamin C, tranexamic acid, polydeoxynucleotides, and glutathione to the cross-linked gel and mix well to obtain the final product, a dermal filler; wherein the active ingredients have a nicotinamide concentration of 0.3 mg / mL, a vitamin B1 concentration of 5 mg / mL, a vitamin B2 concentration of 0.001 mg / mL, a vitamin C concentration of 2 mg / mL, a tranexamic acid concentration of 3 mg / mL, and a polydeoxynucleotide and glutathione concentration of 5 mg / mL.
[0042] Example 3:
[0043] Step 1: Preparation of polyester microspheres:
[0044] 1) Take the molecular weight (Mw) as 3×10 4 Da of PDLA material and molecular weight (Mw) is 1.5×10 4 The PLGA material of Da is dissolved in acetone (or chloroform) solvent to form a polyester material solution, in which the molecular weight is 3×104 The PDLA mass fraction of Da is 15% and the molecular weight is 1.5×10 4 The mass fraction of Da's PLGA was 5%; the mass ratio of high molecular weight PDLA to low molecular weight PLGA was 3:1;
[0045] 2) adding the polyester material solution to a 4% by mass aqueous solution of SDS (Tween 80 may also be used as a substitute) and homogenizing once at 3000 rpm to complete the preparation of polyester material microspheres, wherein the volume ratio of the polyester material solution to the SDS aqueous solution is 1:2;
[0046] Step 2: Add the polyester material microspheres to the mixed protein solution, then add NHS ester, and stir at 300 rpm for 2.5 hours to complete the preparation of composite microspheres, wherein the mass volume ratio (W / V) of the polyester material microspheres to the mixed protein solution is 1:2, where the unit of mass is g and the unit of volume is mL; the mass fraction of NHS ester in the reaction system is 1%; the mass fraction of recombinant collagen in the mixed protein solution is 20%, and the mass fraction of recombinant elastin is 10%;
[0047] Step 3: Add the polyester composite microspheres to a 30% sodium hyaluronate solution and mix evenly. Then add divinyl sulfone (DVS), cross-link at 60°C for 24 hours, and then dialyze and wash to remove the cross-linking agent residue to obtain a cross-linked gel, wherein the mass-to-volume ratio (W / V) of the polyester composite microspheres to the sodium hyaluronate solution is 3:2, where the unit of mass is g and the unit of volume is mL; the mass fraction of divinyl sulfone (DVS) in the reaction system is 5%;
[0048] Step 4: Add the active ingredients niacinamide, vitamin B1, vitamin B2, vitamin C, tranexamic acid, and polydeoxynucleotide to the cross-linked gel and mix well to obtain the final product, a dermal filler; wherein the final concentration of niacinamide is 10 mg / mL, the final concentration of vitamin B1 is 20 mg / mL, the final concentration of vitamin B2 is 0.1 mg / mL, the final concentration of vitamin C is 50 mg / mL, the final concentration of tranexamic acid is 50 mg / mL, and the final concentration of polydeoxynucleotide is 50 mg / mL.
[0049] Comparative Example 1
[0050] This comparative example is the same as Example 1, except that: in step 1, a 1.0×10 4 The PCL mass fraction of Da is 10%, and the molecular weight (Mw) is 2.5×10 4 Da's PCL material.
[0051] Comparative Example 2
[0052] This comparative example is the same as Example 2, except that: in step 1, a molecular weight (Mw) of 1.8×10 4 The mass fraction of PLLA of Da is 5%, and the molecular weight (Mw) is 0.5×10 4 The mass fraction of Da PCL is 1%, and the mass ratio of high molecular weight PLLA to low molecular weight PCL is 5:1.
[0053] Comparative Example 3
[0054] This comparative example is the same as Example 2, except that: in step 1, a molecular weight (Mw) of 1.8×10 4 The mass fraction of PLLA of Da is 2%, and the molecular weight (Mw) is 0.6×10 4 The PCL mass fraction of Da is 12%, and the mass ratio of high molecular weight to low molecular weight materials is 1:6.
[0055] Comparative Example 4
[0056] This comparative example is the same as Example 1, except that step 2 is not included, that is, the step of adding microspheres to the mixed protein solution is missing.
[0057] Comparative Example 5
[0058] This comparative example is the same as Example 1, except that in step 2, the mass fraction of the recombinant collagen in the mixed protein solution is 30%, and the mass fraction of the recombinant elastin is 10%.
[0059] Comparative Example 6
[0060] This comparative example is the same as Example 1, except that in step 2, the recombinant collagen content in the mixed protein solution is 3%, and the recombinant elastin content is 1%.
[0061] Comparative Example 7
[0062] This comparative example is the same as Example 1, except that the cross-linking preparation method in step 3 is different from that in Example 1. Specifically, PCL composite microspheres are prepared according to the method of steps 1 to 2 in Example 1; PEGDE is then added to a 10% sodium hyaluronate solution, wherein the mass fraction of PEGDE in the reaction system is 2.5%, cross-linked at 45°C for 4 hours, and then washed with ethanol to remove the cross-linking agent residue to obtain a cross-linked gel; PCL composite microspheres and active ingredients are then added to the cross-linked gel, mixed evenly, and a final product is prepared, wherein the mass-to-volume ratio (W / V) of PCL composite microspheres to cross-linked gel is 2:3, wherein the unit of mass is g and the unit of volume is mL, and the remaining operating steps are the same as in Example 1.
[0063] Performance Testing
[0064] 1. In vitro degradation test of fillers and subcutaneous implantation test in New Zealand rabbits
[0065] The filler prepared by the present invention was subjected to an in vitro degradation test and a New Zealand rabbit subcutaneous implantation test, and Examples 1-3 were compared with Comparative Examples 1, 2 and 3.
[0066] The specific method of the in vitro degradation test is as follows: 2 g of the dermal fillers prepared in Examples 1-3 and Comparative Examples 1-3 were added to 20 mL of PBS buffer, and then placed in a 37°C incubator. The pH was tested at 1 M, 3 M, 6 M, 9 M, 12 M, 15 M, 18 M, 21 M, and 24 M, respectively.
[0067] The specific method of the New Zealand rabbit subcutaneous implantation test is as follows: the filler products prepared in Examples 1-3 and Comparative Examples 1-3 are injected into the subcutaneous tissue of New Zealand rabbits using a 27G injection needle, with a single injection of 0.5 ml. Histological sections are then taken at 6M, 12M, 18M, and 24M for HE staining and evaluation.
[0068] Since polyester materials will produce a large amount of acidic substances during degradation, monitoring the pH change over time can indirectly reflect the time when acidic substances in polyester materials accumulate. Figure 1 It can be seen that the pH of the filler products prepared in Examples 1-3 changes slowly from the initial stage to the stage of 24M, and there is no rapid drop in pH. However, the pH of the product prepared in Comparative Example 1 drops rapidly to about 7.0 when placed for 3M, the pH of Comparative Example 3 shows a rapid downward trend when placed for 6M, and the pH of Comparative Example 2 shows a rapid downward trend when placed for 18M, indicating that a large amount of acidic substances accumulate in the fillers prepared in Comparative Examples 1-3, resulting in a rapid drop in pH. In particular, the pH of the products prepared in Comparative Examples 1 and 3 changes significantly in a short period of time.
[0069] The results of histological section staining of New Zealand rabbit subcutaneous implantation test are as follows Figure 2 As shown in the results, no obvious inflammatory cells were observed in the subcutaneous tissues at 6M, 12M, 18M, and 24M after the fillers prepared in Examples 1 to 3 were injected. However, in the histological photograph of the sample taken at 6M in Comparative Example 1, the histological photograph of the sample taken at 18M and 24M in Comparative Example 2, and the histological photograph of the sample taken at 12M in Comparative Example 3, inflammatory cells and macrophage infiltration were clearly seen, indicating that tissue inflammatory reactions occurred after the fillers prepared in Comparative Examples 1-3 were implanted.
[0070] Combine Figure 1 and Figure 2The results show that Comparative Examples 1-3 all experienced accumulation of acidic substances, leading to tissue inflammatory reactions. This suggests that the use of polyester materials containing only a single molecular weight (Comparative Example 1) and the use of inappropriately proportioned polyester materials with varying molecular weights (Comparative Examples 2 and 3) resulted in an imbalance between the rate at which the polyester material degraded to produce acidic substances and the body's natural metabolic rate, leading to the accumulation of acidic substances and, in turn, delayed inflammatory reactions. The dermal fillers prepared in Examples 1-3, however, precisely controlled the proportions of polyester materials with varying molecular weights, ensuring that the rate at which the polyester material degraded to produce acidic substances matched the body's metabolic rate, significantly reducing the likelihood of tissue inflammatory reactions.
[0071] 2. Push test
[0072] The fillers prepared in Examples 1-3 and Comparative Examples 4-7 were placed in a syringe and subjected to an extrusion test at a speed of 30 mm / min using a 27G injection needle. The extrusion force was measured using a universal testing machine, and the samples after extrusion were observed under a microscope (10X) to evaluate the aggregation of the microspheres.
[0073] The results of microscope observation of the sample after pushing are as follows Figure 3 As shown, the results show that the microspheres in the fillers prepared in Examples 1 to 3 are evenly dispersed in the gel matrix without aggregation, while the microspheres in the fillers prepared in Comparative Examples 4, 6, and 7 exhibit varying degrees of microsphere agglomeration. This indicates that the cross-linking system formed between the polyester composite microspheres and sodium hyaluronate in Comparative Examples 4 and 6-7 is not stable enough to withstand the mechanical stress during the pushing process. The microspheres in the filler prepared in Comparative Example 5 exhibit irregular shapes under a microscope (indicating that the microspheres are fragmented), which may be due to the fact that the amount of loaded protein exceeds the appropriate range, resulting in excessive cross-linking between the polyester composite microspheres and sodium hyaluronate in Comparative Example 5, reducing their toughness and making them prone to fragmentation when subjected to pushing stress.
[0074] The results of the pushing force test are as follows Figure 4 As shown, the results show that the fillers prepared in Examples 1 to 3 ( Figure 4 .A~C) The pushing force is between 15~25N, and the force fluctuation range is less than ±3N, which shows that the pushing process is smooth and there is no jamming phenomenon; the fillers prepared in Comparative Examples 4, 6, and 7 ( Figure 4.D, F, G) pushing forces all exceed 40N, among which the pushing force of Comparative Example 4 fluctuates in the range of 55 to 90N, and the fluctuation range of Comparative Example 6 is 50 to 70N, indicating that there is a significant change in resistance during the pushing process and the injection is not smooth; the average pushing force of Comparative Example 7 is 65N, and its pushing force is relatively high, which is not conducive to actual operation; although the average pushing force of Comparative Example 5 is 18N, combined with the results of microscopic observation, it can be seen that the microsphere breakage rate during the pushing process is as high as more than 40%, and Comparative Example 5 is not suitable for use as a filler product.
[0075] pass Figure 3 and Figure 4 The test results show that in Comparative Example 4, because no protein was loaded on the polyester material microspheres, there was a lack of active sites for stable cross-linking with sodium hyaluronate, resulting in the microspheres being unable to maintain a stable dispersed state when subjected to force and agglomeration. In Comparative Example 6, due to the insufficient amount of protein loaded on the microsphere surface (only 35% of the average value of the embodiment), the number of active groups was limited, resulting in a loose cross-linked structure. When subjected to external mechanical stress, the microspheres were very easy to agglomerate. Comparative Example 7 uses a preparation process that first cross-links sodium hyaluronate and then mixes the microspheres. The microspheres are mainly supported by cross-linked sodium hyaluronate. There is only a physical wrapping effect between the microspheres and the gel matrix, and there is a lack of chemical cross-linking. Under the action of the pushing force, the microspheres are easy to break away from the initial position and aggregate. The pushing test and microscopic observation results of Examples 1-3 show that the present invention forms a stable three-dimensional network structure by cross-linking the protein loaded by the polyester material composite microspheres with sodium hyaluronate, which can effectively resist the pushing force during the injection process, ensuring smooth injection while maintaining uniform dispersion of the microspheres and avoiding aggregation.
[0076] 3. Rat subcutaneous implantation test
[0077] The dermal fillers prepared in Examples 1-3 and Comparative Examples 4 and 6 were subjected to subcutaneous implantation in rats. The specific method was as follows: 0.5 mL of the prepared product was injected subcutaneously into the skin of SD rats using a 27G needle. Skin elasticity was measured at 6 μM using a multifunctional skin tester. Histological sections were then sectioned and immunohistochemically stained, and the proportion of collagen and elastin in the tissue was quantitatively analyzed using ImageJ. Table 1 shows the collagen and elastin content test results for the fillers prepared in Examples 1-3 and Comparative Examples 4 and 6 six months after implantation. Table 2 shows the skin elasticity test results for the fillers prepared in Examples 1-3 and Comparative Examples 4 and 6 six months after implantation.
[0078] The data in Tables 1 and 2 show that, six months after implantation, the collagen and elastin content, as well as the skin elasticity test results, of Examples 1-3 were significantly higher than those of Comparative Examples 4 and 6. The collagen content was 13.12% higher than in the Comparative Examples, the elastin content was 1.95% higher than in the Comparative Examples, and the elasticity test results were 15.7% higher. This indicates that more collagen and elastin were produced in the subcutaneous tissue of the rats after implantation of Examples 1-3. Further analysis reveals that the polyester material in Comparative Example 4 is consistent with the fact that the microspheres are not loaded with functional proteins. After implantation, the microspheres can only stimulate the body's own synthesis of collagen and elastin through physical contact with tissue, a relatively limited stimulating effect. Furthermore, the microspheres in Comparative Example 6 are loaded with too little protein, resulting in an insufficient number of active groups, such as amino and carboxyl groups, making it difficult for them to fully interact with tissues. The dermal fillers prepared in Examples 1-3, with functional proteins such as recombinant collagen and recombinant elastin loaded on the microspheres' surfaces, not only act as "templates" to directly participate in the construction of the extracellular matrix after implantation, accelerating collagen and elastin deposition, but also activate intracellular signaling pathways (such as the TGF-β / Smad signaling pathway) by releasing active fragments, promoting fibroblast proliferation and differentiation, thereby significantly improving the efficiency of collagen and elastin synthesis. Furthermore, the cross-linked network formed by these functional proteins and sodium hyaluronate provides a stable support structure for the newly synthesized extracellular matrix, further enhancing skin elasticity. This is the fundamental reason why Examples 1-3 significantly outperform Comparative Examples 4 and 6 in terms of collagen and elastin content, as well as skin elasticity testing.
[0079] Table 1 Detection of collagen and elastin content 6 months after implantation (N=10) (*, # represent P<0.05)
[0080]
[0081] Table 2 Elasticity test 6 months after implantation (N=10) (* represents P<0.05)
[0082]
[0083] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment based on the technical essence of the invention shall still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing polyester composite microspheres, characterized in that: The following steps are involved: Step 101: dissolving a high molecular weight polyester material and a low molecular weight polyester material in an organic solvent to obtain a polyester material solution; adding the polyester material solution to an emulsifier solution, and homogenizing and emulsifying at 1000-3000 rpm to obtain polyester material microspheres; the mass ratio of the high molecular weight polyester material to the low molecular weight polyester material is 1:3-3:1; Step 102: Add the polyester material microspheres described in step 101 to a mixed protein solution containing recombinant collagen and recombinant elastin, add crosslinker A, and stir the reaction system to obtain polyester material composite microspheres; the mass-to-volume ratio (W / V) of the polyester material microspheres and the mixed protein solution is 1:(2-5), where the unit of mass is g and the unit of volume is mL.
2. The method for preparing polyester composite microspheres according to claim 1, characterized in that: The polyester material is one of polycaprolactone (PCL), poly L-lactic acid (PLLA), poly D-lactic acid (PDLA) or poly lactic acid-glycolic acid copolymer (PLGA); the molecular weight of the high molecular weight polyester material is 1.8×10 4 ~3.0×10 4 Da, the molecular weight of the low molecular weight polyester material is 0.5×10 4 ~1.5×10 4 Da; the organic solvent is one of dichloromethane, ethyl acetate, acetone or chloroform; the mass fractions of the large and small molecular weight polyester materials in the polyester material solution are both 1% to 15%.
3. The method for preparing polyester composite microspheres according to claim 1, wherein: The emulsifier is polyvinyl alcohol (PVA), hydroxypropyl methylcellulose (HPMC), sodium lauryl sulfate (SDS) or Tween 80; the volume ratio of the polyester material solution to the emulsifier solution is 1: (2-25), and the mass fraction of the emulsifier is 0.01%-4%.
4. The method for preparing polyester composite microspheres according to claim 1, wherein: The mass fraction of the recombinant collagen in the mixed protein solution is 5% to 20%, and the mass fraction of the recombinant elastin is 0.5% to 10%.
5. The method for preparing polyester composite microspheres according to claim 1, characterized in that: The crosslinking agent A is 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC), genipin or 3-mercaptopropane-N-hydroxysuccinimide ester (NHS ester); the mass fraction of the crosslinking agent A in the reaction system is 0.01% to 1%; the stirring speed is 50 rpm to 300 rpm, and the time is 0.5h to 2.5h.
6. A dermal filler, characterized in that: The raw materials of the dermal filler include the polyester material composite microspheres prepared according to any one of claims 1 to 5, and also include sodium hyaluronate solution and active ingredients.
7. The dermal filler according to claim 6, characterized in that: The mass fraction of the sodium hyaluronate solution is 5% to 30%, and the mass-to-volume ratio (W / V) of the polyester composite microspheres to the sodium hyaluronate solution is 3:(2-27), where the unit of mass is g and the unit of volume is mL.
8. The dermal filler according to claim 6, characterized in that: The active ingredients include one or more of the following: recombinant collagen, recombinant elastin, nicotinamide, vitamin B1, vitamin B2, vitamin C, glycine, proline, lysine, tranexamic acid, polydeoxynucleotide and glutathione.
9. A method for preparing the dermal filler according to claim 6, characterized in that: include: Step 1: Add polyester composite microspheres to sodium hyaluronate solution and mix evenly, add crosslinking agent B, crosslink at 20-60° C. for 1-24 hours, and then wash to remove crosslinking agent residue to obtain a crosslinked gel; Step 2: Add active ingredients to the cross-linked gel in step 1 to obtain a dermal filler.
10. The method according to claim 9, characterized in that The crosslinking agent B in step 1 is divinyl sulfone, polyethylene glycol diglycidyl ether (PEGDE) or 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC), and the mass fraction of the crosslinking agent B in the reaction system is 0.5% to 5%.
Citation Information
Patent Citations
Amino-modified poly-L-lactic acid drug-loaded microspheres as well as preparation method and application thereof
CN117838922A